Association between bullying victimization and e‐cigarette use among German students. Issue 4 (8th February 2021) - Hansen, Julia; Morgenstern, Matthis; Isensee, Barbara; Galimov, Artur; Hanewinkel, Reiner
Abstract: This study examined the association between bullying victimization and e‐cigarette use. Data from a 2019–2020 German student survey were used ( N  = 16, 476). The target population consisted of students enrolled in grades 5–10, with a mean age of 13.1 years ( SD  = 1.8), and equal gender distribution (49.5% female). Mixed‐effect multivariable logistic regression models were used to examine the association between bullying victimization (attacked physically, assaulted verbally, experienced relational bullying, sexual harassment, cyberbullying) and current e‐cigarette use. The multivariable analysis controlled for age, sex, sensation‐seeking, socioeconomic status, school performance, type of school attended, and substance use (current cigarette smoking, hookah smoking, and alcohol drinking). Overall 510 (3.7%) students reported current use of e‐cigarettes. The odds for using e‐cigarettes increased each step of being bullied from "never, " "rarely, " "sometimes, " "once a week, " to "several times a week" by 2.03 (95% confidence interval [CI]: 1.81, 2.29) in the unadjusted model, and by 1.46 (95% CI: 1.24, 1.71) in the covariate‐adjusted model. Data indicate an empirical association between victimization and e‐cigarette use among German students. Design limitations prevent the conclusion of a causal relationship, calling for well‐designed longitudinal studies to investigate the temporal sequence between victimization and e‐cigarette use.